Simulation and data fusion of cardiovascular signals for clinical diagnosis - Loh, Shin Wah. (2008)
The objective of this reserach aim to tackle this information overload problem, by devising a clinical diagnostic tool which will combine signals from multiple monitoring devices and help physicians in the decision making process.